Purple sweet potato (Ipomea Batatas P.) as dentin hypersensitivity desensitization gel - Chariza Hanum Mayvita Iskandar; Hardita Bicevani Mulya; Windy Pretyani Kusumawati; Andina Rizkia Putri Kusuma (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Dentin hypersensitivity is a short sharp sense of pain in the teeth when exposed to excitatory stimulus. A total of 74% of world population experiencing dentin hypersensitivity. Home treatment topical desensitization is rarely found in Indonesia. The use of dentrifice is less practical because it must be done with regular brushing. Indonesia has abundant natural resources, one of which is purple sweet potato. Purple sweet potato (Ipomea Batatas P.) has highest potasium ions compared to other foodstuffs. Potassium ions can be a solution of dentin hypersensitivity by temporary blocking the suffix pulp nerve impulses. Purpose: The research objective was to determine the effectiveness of the 10% purple sweet potato extract gel of the dental pain threshold score. Method: An experimental study carried out by dental pain threshold score measurements using vitality tester into the teeth with gum recession. Samples included 32 respondents with a single blind and pre-post test control group design. They were divided into treatment group and negative control group. Paired T-test and Wilcoxon were used as data analysis. Result: The results showed dental pain threshold score increasing either in treatment group and negative control, although not as significant as in the treatment group. Conclusion: 10% purple sweet potato extract gel containing potassium ions is able to reduce the pain of dentin hypersensitivity.